Nomenclatural standards of black currant cultivars bred by Sverdlovsk Horticultural Breeding Station. Part II - L. V. Bagmet; E. M. Chebotok; A. V. Shlyavas (Аграрная наука Евро-Северо-Востока)
For the first time in Russia, N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) has initiated and is working on the creation of nomenclatural standards of domestic cultivars. The nomenclatural standard confirms the originality of the cultivar and protects the copyright of its creators. The article presents the nomenclatural standards of 8 black currant (Ribes nigrum L.) varieties bred at Sverdlovsk Horticultural Breeding Station, that are undergoing State variety testing: Ataman (WIR-54113), Viktorina (WIR-54116), Voevoda (WIR-54117), Dobrokhot (WIR-54120), Kornet (WIR-54124), Mushketer (WIR-54126), Napev Uralskiy (WIR-54135), Staratel (WIR-54130). Herbarium samples the plant material for which has been selected directly by the author of these varieties in the collection of the originator organization are taken as nomenclature standards. In addition to the description and photos of the nomenclature standards, the distinctive taxonomic and economically valuable features of each variety are given. The created nomenclature standards in the amount of 14 herbarium samples are made in accordance with the recommendations of the International Code of Nomenclature for Cultivated Plants (ICNCP), registered in the database "VIR Herbarium" and included to the type collection of the Herbarium of cultivated plants of the world, their wild relatives and weeds (WIR).